Competitive demands and performance-determining variables in Olympic ski mountaineering - Wei, X.; Zheng, X.; Zhu, H.; Vigh-Larsen, J. F.; Mohr, M.; Krustrup, P.; Chen, X. (International Journal of Sports Physiology and Performance, 2025)
Purpose: To investigate the competitive demands and performance-determining variables in the Sprint and Mixed-Relay formats in male and female ski mountaineers.